ANALISIS PERBANDINGAN KINERJA KEUANGAN BANK DEVISA DAN BANK NON DEVISA DI INDONESIA - Azlina Azis; Hardi -; Rofika - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The study purposed to examine and analyze the differences in ROA, ROE, LDR and CAR between foreign banks and non-foreign exchange banks in Indonesia. Objects in this study is a Foreign Exchange Bank and Non-Foreign Exchange Bank in Indonesia 2008-2012 Period. The sample in this study as many as 24 by using purposive sampling method and type of data is secondary data. The data used is derived from the existing data, as for the analytical method used was Paired Sample t-test. The results of the current testing shows that from 2008-2012 ROE, LDR and CAR had different ratios between the financial performance of foreign banks and non-foreign exchange banks. This happens because foreign banks are not optimally exploit and gain profit opportunities of transactions using foreign currency. While ROA ratios did not different between the financial performance of foreign banks and non- foreign exchange banks.Keywords: Return On Asset, Return On Equity, Loan to Deposit Ratio, Capital Adequacy Ratio and Financial Performance